Thermoelectric effect as waste heat recovery technology / Nur Fatiah Mohd Rosli - Mohd Rosli, Nur Fatiah (UiTM Press, 2014)
The aim of this research is to utilize waste heat as an alternative source of power, to analyse thermoelectric effect principle as waste heat recovery technology and to apply the thermoelectric effect as waste heat recovery to household appliances. The scope of study for this research is to understand the principle, function and concept of the thermoelectric effect, testing either waste heat can be as alternative energy and simulation on thermoelectric performant using Matlab/Simulink. Waste heat has wide of the range, in this research will focus on utilizing waste heat from household appliances, refrigerator compressor. The use of thermoelectric generators as waste heat recovery rapidly increase in recent years thus, with review initially through the university library using the OPAC system to find book related to the research, journal abstract and internet search on the research that has been done. The waste heat from the low temperature of the heat can be reused or utilize by using thermoelectric effect principle. Therefore, the thermoelectric effect can call as the waste heat recovery technology.